Equivalence within the Dynamic Translation Model (DTM): Default Equivalence Position, Equivalence Range, Initiator’s Instructions, and Translational Norms (2016)
Within the framework of a Dynamic Translation Model (DTM) (Bolaños, 2008) an attempt is made to show how equivalence is actually a key concept for the definition and explanation of translation. Central to this modern approach to translational equivalence is the relationship that holds between the Default Equivalence Position (DEP), Equivalence Range (ER), Initiator’s Instructions (II), and Translational Norms (TN). In this approach it is also clear that the explanatory power of the concept of equivalence is widened and it becomes suitable to adequately account for the different types of equivalence that are established in different text types (literary, scientific, and appellative texts), when several translational strategies are used, e.g. by resorting to domesticating or foreignizing linguistic resources.